THE EFFECT OF ISLAMIC WORK ETHICS ON EMPLOYEE LOYALTY OF YAYASAN NURUL HAYAT SURABAYA - Sheila Ayu Pramesti Permatasari; Ririn Tri Ratnasari (Universitas Airlangga, 2020)
This study aims to determine the effect of Islamic work ethics on employee loyalty at Nurul Hayat Foundation in Surabaya. This study uses a quantitative approach. Data collection techniques are by distributing questionnaires to employees of Nurul Hayat Surabaya. The analysis technique used is SEM PLS by conducting a non-probability sampling technique used in sampling in this study, namely the purposive sampling technique. The results of this study indicate that Islamic work ethics has a significant influence on employee loyalty.Keywords: Ethics, Employee Loyalty, Nurul HayatREFFERENCE Ahmad, Shukri dan Yusuf Owoyemi, Musa. (2012). The concept of Islamic work ethic: An analysis of some salient points in the prophetic tradition. International Journal of Business and Social Science, 3(20),116-123.Ali, A. (2001). Scaling an Islamic work ethics. The Journal of Social Psychology, 128(5), 575-83.Ali, A. J., & Al-Kazemi, A. A. (2007). Islamic work ethic in Kuwait. Cross Cultural Management: An International Journal, 14(2), 93–104.Ali, A.J., dan Owaihan, A.A. (2008). Islamic work ethic: A critical review. Cross Cultural Management: An International Journal, 15(1), 5-19.Anwar Prabu Mangkunegara. (2004). Manajemen sumber daya manusia perusahaan. Bandung: PT Remaja Rosdakarya.Chang, C. C., C. M. Chiu, et al. (2010). The effect of TQM practices on employee satisfaction and loyalty in government. Total Quality Management, 21(12), 1299-1314.Faqih, Ainur Rahim. (2011). Bimbingan dan Konseling dalam Islam. Jakarta: UII press.Hart, D. W. and J. A. Thompson. (2007). Untangling employee loyalty: A psychological contract perspective. Business Ethic Quarterly, 17(2), 297-323.Hasibuan, Malayu S.P. (2010). Manajemen sumber daya manusia. Jakarta: PT Bumi Aksara.Kirana, K.C., Ratnasari, R.T. (2017). Evaluasi kinerja sumber daya manusia (SDM). Yogyakarta: Gosyen Publishing.Marri, M.Y.K. (2012). The Impact of Islamic work ethics on job satisfaction and organizational commitment: A study of agriculture sector of Pakistan. IJJBBS, 2(12), 37-49.Sugiyono. (2012). Metode penelitian kuantitatif kualitatif dan R&D. Bandung: Alfabeta.